Efek Penambahan Plutonium pada Sel Bahan Bakar MOX terhadap Performa Reaktor GFR 250MWth - Muhammad Aldi Kurniawan; Menik Ariani; Monado, Fiber; Johan, Akmal; Kaban, Hadir (Universitas Andalas, 2025)
A fast-type reactor that operates on high-speed neutrons, GFR (Gas-cooled Fast Reactor) can produce various fissile materials and fertilizers. This production capability is very beneficial for the stability of nuclear fuel in the reactor core, especially reactors that use closed cycles such as GFR. Plutonium (Pu) from the residue from burning reactors such as PWR or LWR can be used as a mixed fuel to increase fissile nuclides in MOX fuel. MOX (Mixed Oxide) is a mixture of uranium (U) and plutonium (Pu) in certain amounts. The composition of plutonium (Pu) in MOX greatly influences the level of fuel combustion in the core at the start of operation. The research aims to vary the percentage of plutonium (Pu) to enable design adjustments to maximize fuel use efficiency. Simulations were conducted computationally to determine the performance of each percentage of Pu used in MOX. Depletion calculations were carried out for 10 years using the OpenMC code and ENDF/B VIII.0 nuclear data. The research results show that the best design performance is at a Pu percentage of 11% which is determined based on the range of effective multiplication factor (keff ) values and excess reactivity and is in line with expectations.